The Effect of Nickel Mass Variations on the Capacitance of Supercapacitor Electrodes Made of Graphite Nanoparticles - Hari Rahmadani; Reza Akbar Pahlevi; Soumen Mandal; Changiz Dehghanian; Shaymaa Hadi Al-Rubaye; Abolanle S. Adekunle; Ebru Koroglu (Tinta Emas Publisher, 2025)
Energy storage based on energy and power density. Supercapacitors are one of the most promising types of energy storage device, because it has a higher energy density than dielectric capacitors and a higher power density than rechargeable batteries. In this study, Nickel and Graphite were used which were dissolved in Dimethyl Acetamide (DMAC) solvent. Ni/Graphite composites were characterized by XRD to determine the crystalline phase, SEM to determine morphology, and Charge-Discharge to determine electrochemical properties. XRD pattern analysis results, it was found that the highest intensity peak was at an angle of 26° and had a crystal size of 59.7 nm. Identification of SEM images on Ni/Graphite composites resulted in porosity of 71.4%, 71.8%, and 72%. Electrochemical performance of the electrode resulted in specific capacitance and optimum energy density at 20 %wt nickel mass variations of 71.8 Fg−1 and 69.65 Wh.Kg−1. The specific capacitance resulting from the Nickel/Graphite composite electrode is directly proportional to the addition of nickel mass.